2021
DOI: 10.1177/00220345211037220
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and the Risk of Periodontitis: A Population-Based Cohort Study

Abstract: Dementia and Alzheimer’s disease (AD) are proposed to be comorbid with periodontitis (PD). It is unclear whether PD is associated with dementia and AD independent of confounding factors. We aimed at identifying the relationship between the longitudinal risk of developing PD in a cohort of patients with dementia and AD who did not show any signs of PD at baseline. In this retrospective cohort study, 8,640 patients with dementia without prior PD were recruited, and 8,640 individuals without dementia history were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 39 publications
2
44
1
Order By: Relevance
“…On the other hand, the age‐dependent increase in fibromyalgia incidence in our study was in line with previous studies 13,14,24 . In our study, patients aged below 30 had the greatest risk of developing fibromyalgia following periodontitis, which is similar to previous studies suggesting that younger periodontitis cases are often assocaited with more active host immune responses and more severe periodontal destruction 25 . Although in the present study, patients of both sexes and all age groups had significantly greater risks for fibromyalgia following periodontitis, population subgroups with more inflammatory traits for periodontitis 23,25 were predisposed to even greater risks of fibromyalgia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the age‐dependent increase in fibromyalgia incidence in our study was in line with previous studies 13,14,24 . In our study, patients aged below 30 had the greatest risk of developing fibromyalgia following periodontitis, which is similar to previous studies suggesting that younger periodontitis cases are often assocaited with more active host immune responses and more severe periodontal destruction 25 . Although in the present study, patients of both sexes and all age groups had significantly greater risks for fibromyalgia following periodontitis, population subgroups with more inflammatory traits for periodontitis 23,25 were predisposed to even greater risks of fibromyalgia.…”
Section: Discussionsupporting
confidence: 93%
“…13,14,24 In our study, patients aged below 30 had the greatest risk of developing fibromyalgia following periodontitis, which is similar to previous studies suggesting that younger periodontitis cases are often assocaited with more active host immune responses and more severe periodontal destruction. 25 Although in the present study, patients of both sexes and all age groups had significantly greater risks for fibromyalgia following periodontitis, population subgroups with more inflammatory traits for periodontitis 23,25 were predisposed to even greater risks of fibromyalgia. Further examining the link between perodontitis and fibromyalgia revealed that fibromyalgia patients who never had periodontitis were at greater risk of developing periodontitis.…”
Section: Discussioncontrasting
confidence: 55%
“…Hence misclassification bias could exist. However, we tried our best to address misclassification bias by utilizing definitions of exposure and outcome that has been validated by previous studies ( Chang et al, 2016 ; Chen et al, 2016 ; Ling et al, 2021 ; Ma et al, 2021 ). The definition of GERD in this study included not only ICD-9 diagnosis records, but also prescription of PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort study, we employed a nationwide population-based registry to provide epidemiological evidence on the risks of new-onset ED in patients with HPV infection. The effect of measurable confounders was minimized by PS matching [ 71 , 72 , 73 , 74 , 75 ]. Sensitivity and negative control analyses were conducted to manage residual confounding and to ascertain the impact of HPV infection on ED development.…”
Section: Discussionmentioning
confidence: 99%